Cardiovascular Disease Risk Factors Among Children and Adolescents With Depression - Korczak, Daphne J.; Cleverley, Kristin; Birken, Catherine S.; Pignatiello, Tony; Mahmud, Farid H.; McCrindle, Brian W. (Frontiers in Psychiatry, 2021)
Aim: To examine CVD risk factors among children and adolescents with Major Depressive Disorder (MDD). Methods: A cross-sectional study of 77 children and adolescents (mean age 14.1 years, 74% female) referred to a pediatric depression program. MDD was assessed using a semi-structured diagnostic interview. Cardiovascular assessments included family cardiovascular disease (CVD) history, cigarette smoking, body mass index (BMI), blood pressure, lipid and glucose concentrations. CVD risk factors among healthy weight and overweight/obese participants were compared. Results: Forty-six percent of participants had a family history of early CVD. On examination, 25% of participants had a BMI in overweight/obese range, and 25% of children had pre-hypertension (14%) or hypertension (11%). Total cholesterol levels were elevated among 28% of participants. Overweight/obese participants had increased non-HDL cholesterol concentrations compared with healthy-weight participants (36% vs 10%, p=.01). There were no significant differences between healthy and overweight/obese groups for other CVD risk factors, including HDL cholesterol concentration, plasma glucose concentration, hypertension, cigarette smoking, and family history of early CVD. More than half (52%) of participants had at least two CVD risk factors. Conclusion: CVD risk factors are prevalent among children and adolescents with MDD. Routine CVD risk factor screening may be warranted among MDD youth, regardless of BMI, and may provide a valuable opportunity for prevention of future CVD.